Upper Facial Anastomoses Between the External and Internal Carotid Vascular Territories – A 3D Computed Tomographic Investigation. (19th March 2022) - Li, Zhen-Hao; Alfertshofer, Michael; Hong, Wei-Jin; Li, Xin-Rui; Zhang, You-Liang; Moellhoff, Nicholas; Frank, Konstantin; Luo, Sheng-Kang; Cotofana, Sebastian
Abstract: Background: Facial regions with a high risk for causing injection-related visual comprise are dual-supply vascular areas such as the nose, glabella, and forehead. These regions have in common that they receive arterial blood supply both by branches of the internal (ICA) and the external carotid artery (ECA). Objective: The authors sought to investigate the anastomotic pathways between ICA and ECA branches in the upper face. Methods: Postmortem computed tomographic angiographic scans of n = 38 Chinese non-embalmed hemifaces (25 males, 13 females; mean age, 37.79 [11.8] years; mean BMI, 21.90 [2.3] kg/m 2 ) were conducted. Data analysis relied on the calculation of depth, distances, and pathways of forehead and temporal arteries to investigate the number of anastomotic connections, the connecting branches, and the layer of connection between ICA and ECA territories. Results: Between ICA and ECA territories, only 1 connection in 57.9%, 2 connections in 31.6%, 3 connections in 5.3%, and 4 and 5 connections in 2.6% each were identified. A superficial connection was observed in 15.8% whereas in 84.2% the anastomotic connection was identified to be both superficial and deep. Conclusions: Adverse events following facial minimally invasive soft-tissue filler injections for aesthetic purposes are not frequent but devastating if they occur. Anatomic knowledge as presented in this study can help to increase awareness of 3-dimensional vascular anastomotic pathways and identify safer injection zones and safer fascial planes. Evidence-based injection techniques should be followed, and safety aspects should be placed over the aesthetic outcome.